The first child with mixed invasive pulmonary Mucor and Aspergillus infection: a case report and literature review - Wang, Shifu; Yang, Shangmin; Ma, Jing; Zhang, Chunyan; Li, Zheng; Wang, Mengyuan; Yu, Wenwen; Liu, Guohua (Frontiers in Medicine, 2024)
Purpose Coinfections or consecutive infections of Mucor and Aspergillus are exceedingly uncommon in children, we report the case to offer the valuable experience for colleagues facing similar situations. Case report This report documents the first recorded case of successful treatment for pulmonary mixed infection in a diabetic girl. Initially, the patient underwent treatment based on voriconazole, but the infection continued to deteriorate. Subsequently, bronchoalveolar lavage fluid culture and metagenomic next-generation sequencing (mNGS) were conducted, leading to a clear diagnosis of simultaneous infection by Aspergillus fumigatus and Rhizopus microsporus. Susceptibility testing revealed fungal resistance to voriconazole. Therefore, a combined treatment regimen of AmB liposomes and isavuconazole effectively eradicated the fungal infection. Conclusion This case underscores the importance of early and precise identification of fungal pathogens, determination of effective antifungal medications, and timely implementation of well-planned therapeutic strategies. Furthermore, we comprehensively reviewed 10 cases of pulmonary mixed infections involving Mucor and Aspergillus, summarizing their characteristics and identifying commonalities.